Social workers' perspectives on people parenting while patients in a secure hospital. Issue 3 (3rd May 2020) - Kalebic, Natasha; Adams, Alex; Bezeczky, Zoe; Argent, Sarah; Bagshaw, Ruth; Taylor, Pamela J.
ABSTRACT: Up to half of the approximately 10, 000 people resident in a UK secure hospital are parents. There are well-established child safeguarding policies, but no model for social work support of parenting. Our study aimed to investigate social workers' experience of secure hospital patients as parents and develop a testable model of good practice. Each social worker in one medium security hospital unit was invited to an individual semi-structured interview about his/her perspectives on patients parenting from the unit. Six social workers participated; all had experience there of patients with and without children. A core concern of 'artificiality' best encompassed the emergent themes covering the nature of the setting, poor mental health with sometimes delusional family life, difficult family dynamics, weakened parenting skills and patient-parent wish for communication inhibited by a sense of stigma. Resolution towards 'naturalness', with improved mental health, communication skills, family dynamics, and reducing confinement was partially achieved during the inpatient stay, much of the change actively facilitated by clinical interventions. While child safeguarding during a parent's secure hospital stay is vital, longer-term psychosocial repair of relationships seems feasible. An actively restorative model envisaged by these social workers offers a testable progression towards responsible parenting.